Postharvest treatments with γ‐aminobutyric acid, methyl jasmonate, or methyl salicylate enhance chilling tolerance of blood orange fruit at prolonged cold storage. (9th August 2019) - Habibi, Fariborz; Ramezanian, Asghar; Rahemi, Majid; Eshghi, Saeid; Guillén, Fabián; Serrano, María; Valero, Daniel
Abstract: BACKGROUND: Blood orange is sensitive to chilling injury (CI) depending on cultivar and storage temperature. Postharvest treatments with γ ‐aminobutyric acid (GABA), methyl jasmonate (MeJA), or methyl salicylate (MeSA) are known to alleviate CI. γ ‐Aminobutyric acid aqueous solution, applied at 20 and 40 mM, was vacuum‐infiltrated at 30 kPa for 8 min at 20 °C. Methyl jasmonate or MeSA vapor treatments were applied separately at 50 and 100 μM by putting the fruit in 20 L plastic containers for 18 h at 20 °C. There have been no reports about postharvest treatments of GABA, MeJA, or MeSA on enhancing the tolerance of 'Moro' blood orange to chilling during long‐term cold storage at 3 °C for 150 days, which was the subject of this study. RESULTS: All treatments significantly alleviated CI symptoms of blood orange manifested by lower electrolyte leakage (EL), malondialdehyde (MDA), hydrogen peroxide (H2 O2 ) concentrations, and higher proline content in flavedo during storage. The largest effects were obtained with 100, 50 μM, and 40 mM for MeSA, MeJA, and GABA, respectively, which enhanced the activity of the antioxidant enzymes catalase (CAT), ascorbate peroxidase (APX) and superoxide dismutase (SOD), and phenylalanine ammonia‐lyase (PAL). On the other hand, these treatments suppressed peroxidase (POD) and polyphenol oxidase (PPO) activities. CONCLUSION: The mechanisms involved in enhancing the tolerance of 'Moro' blood orange to chilling could involve scavenging H2 O2 by increasing the activity of antioxidant enzymes, higher PAL/PPO activity ratio, and osmoregulation by increasing proline content. These changes led to the maintenance of the epidermis structure. This was confirmed by scanning electron microscopy (SEM) micrographs. © 2019 Society of Chemical Industry